The Influence of Value Added Tax (PPN), Luxury Sales Tax (PPnBM), and Progressive Motor Vehicle Tax (PKB) on the Purchasing Power of Electric Vehicles in Bandung City Indonesia - Riyan Saputra; Farhatun Nisa (CV Putra Publisher, 2024)
The transition from conventional vehicles to electric or battery-based vehicles can be facilitated through policy interventions, especially in the field of taxation, aimed at achieving certain goals. This study aims to determine the effect of Value Added Tax (VAT), Luxury Goods Sales Tax (PPnBM), and Progressive Motor Vehicle Tax (PKB) in Indonesia on the purchasing power of electric vehicles in Bandung City, Indonesia. This study uses primary data collected through a questionnaire with a multiple linear regression analysis method. The sampling technique used is purposive sampling, using the Slovin formula which produces 100 respondents. The collected data was processed using SPSS software version 25. The results of this study indicate that partially, VAT and PKB do not have a significant positive effect on the purchasing power of electric vehicles. Meanwhile, PPnBM has a significant positive effect on the purchasing power of electric vehicles. These findings indicate that PPnBM tax incentives are effective in increasing the purchasing power of electric vehicles, while VAT and PKB incentives require evaluation and adjustment in order to better support the transition to electric vehicles. This research provides an important contribution for policy makers to design more effective tax incentives to encourage the adoption of electric vehicles, in order to achieve the targets of reducing emissions and improving environmental sustainability.